POSITION OF MANDIBULAR FORAMEN AND INCIDENCE OF ACCESSORY MANDIBULAR FORAMEN IN DRY MANDIBLES - RAGHAVENDRA V. P.,; BENJAMIN W., (International Journal of Pharma and Bio Sciences, 2015)
To determine the position of mandibular foramen (MF) from various parts of ramus of mandible and the incidence of accessory mandibular foramen (AMF) by studying on dry mandibles to assist dental surgeons to conduct dental procedures. Study was carried out on 100 dry mandibles of which 84 are dentulous and 16 are edentulous. The average distance of MF from the anterior boarder of mandibular ramus was 16.21±2.12 mm (right side) and 16.67±2.34 mm (left side), from posterior boarder of mandibular ramus was 11.08±2.34 mm (right side) and 11.11±2.34 mm (left side). The MF was located 21.38±3.91 mm (right side) and 20.95±3.39 mm (left side) from the mandibular notch. The distance of MF from angle of mandible was 21.48±3.75mm (right side) and 21.08±3.90mm (left side). AMF was present in 9% of mandibles. In 6% single AMF was present and in 3% double foramina were present. The complications such as hemorrhage and paresthesia during oral surgical procedures can be avoided by knowing the exact location of MF and AMF.